2018
DOI: 10.1016/j.colsurfa.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of PEG40St squeeze out from DSPC/PEG40St monolayers at higher molar ratios

Abstract: Mixtures of 1,2 Distearoyl-sn-glycero-3-phosphocholine (DSPC) and polyoxyethylene-40-stearate (PEG 40 St) were prepared at different molar ratios and their miscibility were investigated using Langmuir isotherms. Pure DSPC monolayer exhibited a liquid-condensed (LC) phase whereas PEG 40 St monolayer exhibited liquid-expanded (LE) phase at the air-water interface at 22 ± 2°C. At the collapse pressure of 33 mN/m, the PEG 40 St mean molecular area was calculated to be 28 Å 2 /molecule for 9:1 composition and 50 Å … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…It was shown that microbubble stability can be improved by controlling the conformational changes in the PEG chain of the emulsifier by cooling down the microbubbles to desired temperature upon their production. As we have shown before, the another way to control conformational changes in the PEG chain of the emulsifier is to increase the PEG40St content in the formulation (40,41). Overall, the results suggest that the effect of the conformational changes induced by temperature in the PEG chain of the emulsifier should be taken into account for the design of more stable microbubbles.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It was shown that microbubble stability can be improved by controlling the conformational changes in the PEG chain of the emulsifier by cooling down the microbubbles to desired temperature upon their production. As we have shown before, the another way to control conformational changes in the PEG chain of the emulsifier is to increase the PEG40St content in the formulation (40,41). Overall, the results suggest that the effect of the conformational changes induced by temperature in the PEG chain of the emulsifier should be taken into account for the design of more stable microbubbles.…”
Section: Discussionsupporting
confidence: 60%
“…In those studies, formation of larger dark domains surrounded by emulsifier-rich continuous phase (rich-in fluorophore and therefore brighter) during slow cooling process indicates entrapment of more emulsifier molecules between condensed phase DSPC molecules (deficient in fluorophore and therefore darker) as results of PEG chains enabling to have enough time to extend into the aqueous phase and mix with condensed DSPC molecules, as discussed above. We also showed that conformational changes in the PEG chain of the emulsifier can be controlled by increasing the PEG40St content in the formulation, leading to production of more stable microbubbles (40,41). Figure 8.…”
Section: High Temperaturementioning
confidence: 87%
“…Almost 93%, 82%, and 53% of PEG40 St displaced for the 9:1, 7:3, and 5:5 mixtures, respectively, at the end of the first collapse plateau [29]. Remaining PEG 40 St squeezed out at the end of the second collapse plateau, where 20% of PEG 40 St still contained within the 5:5 composition [29]. Here, a scale was established on the Brewster angle microscopy (BAM) images of the monolayers to better interpret the morphologies of the mixtures.…”
Section: Introductionmentioning
confidence: 95%
“…Plateaus were relatively shorter for the 9:1 mixture and extended significantly by increasing the PEG 40 St content. In our recent paper, we developed a quantification method to estimate the squeeze out amount of PEG 40 St from Langmuir isotherms [29]. Almost 93%, 82%, and 53% of PEG40 St displaced for the 9:1, 7:3, and 5:5 mixtures, respectively, at the end of the first collapse plateau [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation